A method for preparing ultra-transparent flexible PVB resin powder without Tyndall effect

Through the cross -linking response of the modified polyvinyl alcohol solution and the silicane additive, the Tintar effect problem of PVB resin powder in thick membranes is solved, the transparency and high temperature resistance performance is improved, and the production process is simplified, and the cost is reduced.

CN117624654BActive Publication Date: 2025-01-28JIANGSU AOTIANLI NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311670242.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-06
Publication Date
2025-01-28
Estimated Expiration
2043-12-06

AI Technical Summary

Technical Problem

When the PVB diaphragm is thicker, the existing PVB resin powder is prone to Dydar effect, which affects the light transmittance performance of the product, and the production process is complex and the cost is high.

Method used

Polyvinyl alcohol with a model with 092-52 and purifying water is heated and dissolved, combined with catalyst and methamphetamine for esteria bonus to form a modified polyethylene alcohol solution. Improve cross -linking.

Benefits of technology

The flexible PVB resin powder of the Ding Dar effect is achieved, which improves the transparency and high temperature resistance of the product, simplifies the production process, and reduces the cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004592981640000031
    Figure BDA0004592981640000031
  • Figure BDA0004592981640000041
    Figure BDA0004592981640000041
  • Figure BDA0004592981640000051
    Figure BDA0004592981640000051
Patent Text Reader

Abstract

The invention discloses a method for preparing a super-transparent flexible PVB resin powder without Tyndall effect, and belongs to the technical field of PVB resin processing. The invention is used to solve the technical problem that two PVAs in the prior art easily lead to slight differences in the refractive index of the finished product, and when the PVB film is thicker, the Tyndall effect is likely to occur under strong light, affecting the light transmission performance of the product. A method for preparing a super-transparent flexible PVB resin powder without Tyndall effect comprises the following steps: adding polyvinyl alcohol and purified water to a three-necked flask and stirring, raising the temperature of the three-necked flask to 50-60°C, and stirring until the system is dissolved. The present invention selects a polyvinyl alcohol as a raw material, and after modifying it, it is compounded with a polyoxyalkylene with a long straight chain structure to prepare a PVB resin powder that is easy to process and has good sound insulation and noise reduction effects, which not only effectively reduces the yellow index, improves its high temperature resistance, but also avoids the generation of the Tyndall effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PVB resin processing, and in particular to a method for preparing ultra-transparent flexible PVB resin powder without Tyndall effect. Background Art

[0002] The chemical name of PVB resin powder is polyvinyl butyral, which is produced by the reaction of polyvinyl alcohol (PVA) and n-butyraldehyde under acidic conditions. Compared with PVA, PVB has higher temperature resistance and weather resistance, and its chemical structure is stable. It has good tensile and impact resistance. PVB resin powder is widely used in ink, building adhesives, semiconductor MLCC, ceramics and laminated glass.

[0003] With the rapid development of today's society, many safety glasses are needed in the construction, photovoltaic and automobile industries. Of course, PVB resin is indispensable. PVB resin plays a vital role in laminated glass. In the application of laminated glass, people not only pay attention to important mechanical and other safety performance, but also begin to pay attention to comfort experience such as sound insulation and heat insulation. Among them, sound insulation performance has been widely used in the field of architectural and automotive laminated glass in recent years.

[0004] Sound is a sound wave generated by the vibration of an object. It is a wave phenomenon that is transmitted through a medium (air or solid, liquid) and can be sensed by the auditory organs of humans or animals. The object that initially vibrates (vibrates) is called the sound source. Sound vibrates (vibrates) in the form of waves. Sound is the movement formed by the propagation of sound waves through any medium. The human ear can hear sounds of 20-20000Hz. Ordinary PVB resin powder can also play a certain role in sound damping after being made into PVB interlayer with plasticizer, but the effect is not good, and there is not much sound insulation effect on high-frequency human voice and wind noise.

[0005] In the automotive glass industry, in terms of sound insulation, the windshield is usually pressed with sound insulation grade PVB interlayer. This type of sound insulation grade PVB interlayer can effectively reduce 3-5dB compared to ordinary grades. With the growing demand for sound insulation of automotive glass, domestic sound insulation grade PVB interlayer is also ready to go. The production technology for sound insulation grade PVB interlayer is usually multi-layer co-extrusion, which achieves improved sound insulation effect through the composite form of A / B / A, where the B layer is a sound insulation flexible PVB resin with a high plasticizer content.

[0006] Patent CN113861315A applied by China discloses a polyvinyl butyral with sound insulation performance and its preparation method. The polyvinyl butyral includes the following raw materials in parts by weight: 30-35 parts of polyvinyl alcohol, 16-19 parts of n-butyraldehyde, 4-6 parts of catalyst and 0.18-0.3 parts of surfactant. The polyvinyl alcohol is a mixture of high-polymerization polyvinyl alcohol and low-polymerization polyvinyl alcohol. The polymerization degree of the high-polymerization polyvinyl alcohol is 2000-2600, and the polymerization degree of the low-polymerization polyvinyl alcohol is 500-800. The invention has the advantages of low hydroxyl content, excellent sound insulation effect and optical properties. However, the invention requires two combinations of raw materials, the process is cumbersome, and it is easy to cause fluctuations in raw material parameters, affecting the quality of the finished product. The two PVAs are easy to cause slight differences in the refractive index of the finished product. When the PVB film is thicker, the Tyndall effect is easy to occur under strong light, affecting the light transmission performance of the product. Therefore, it is very important to develop a flexible PVB resin without Tyndall effect, simple production process and low cost.

[0007] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing ultra-transparent flexible PVB resin powder without Tyndall effect, which is used to solve the technical problems in the prior art that two types of PVA easily lead to slight differences in the refractive index of the finished product, and when the PVB film is thicker, the Tyndall effect is easily caused under strong light, thereby affecting the light transmission performance of the product.

[0009] The purpose of the present invention can be achieved by the following technical solutions:

[0010] A method for preparing ultra-transparent flexible PVB resin powder without Tyndall effect comprises the following steps:

[0011] S1. Add polyvinyl alcohol and purified water into a three-necked flask and stir. Raise the temperature of the three-necked flask to 50-60°C and stir until the system is dissolved. Lower the temperature of the three-necked flask to 20-30°C and filter to obtain a polyvinyl alcohol solution.

[0012] S2, adding the polyvinyl alcohol solution and the catalyst into a three-necked flask and stirring, lowering the temperature of the three-necked flask to 20-30° C., slowly dropping glacial acetic acid into the three-necked flask, and after the dropping is complete, heat-retaining and reacting for 10-12 hours to obtain a modified polyvinyl alcohol solution;

[0013] S3, adding the modified polyvinyl alcohol solution, surfactant and inorganic acid into a three-necked flask and stirring, lowering the temperature of the three-necked flask to 10-12° C., slowly dropping n-butyraldehyde into the three-necked flask, after the dropping is completed, raising the temperature of the three-necked flask to 56-65° C., keeping the temperature for reaction for 1-3 hours, and obtaining a PVB resin reaction solution;

[0014] The synthetic reaction principle of PVB reaction solution is:

[0015]

[0016] S4. Add silane additive to the three-necked flask containing the PVB resin reaction solution, keep the temperature of the three-necked flask at 56-65° C., stir for 3-5 hours, and perform post-treatment to obtain PVB resin powder.

[0017] Furthermore, in step S1, the weight ratio of polyvinyl alcohol to purified water is 1:24, and the model of the polyvinyl alcohol is 092-53.

[0018] Furthermore, in step S2, the weight ratio of the polyvinyl alcohol solution, the catalyst and the glacial acetic acid is 500:3:1, the catalyst is composed of p-toluenesulfonic acid and zinc chloride in a weight ratio of 1:3, and the dripping rate of the glacial acetic acid is 0.2-0.4 g / min.

[0019] Furthermore, in step S3, the weight ratio of the modified polyvinyl alcohol solution, the surfactant, the inorganic acid and n-butyraldehyde is 500:0.5:5:4, the surfactant is sodium dodecylbenzene sulfonate, and the inorganic acid is 12 mol / L hydrochloric acid.

[0020] Furthermore, the weight ratio of the silane additive in step S4 to the modified polyvinyl alcohol solution in step S3 is 5:700, and the post-treatment operation includes: after the reaction is completed, the temperature of the three-necked flask is lowered to room temperature, 20wt% sodium hydroxide solution is added to the three-necked flask, the system pH is adjusted to 3-4, stirred for 1h, filtered, the filter cake and purified water are mixed and stirred at a dosage ratio of 1g:10mL for 20-30min, filtered, the filter cake is repeatedly washed with purified water 10 times and then transferred to a drying oven at a temperature of 55-65°C, vacuum dried to constant weight, crushed, and passed through a 60-mesh sieve to obtain PVB resin powder.

[0021] Further, the silane additive is processed by the following steps:

[0022] A1. Diethoxymethylsilane, diethoxydimethylsilane and anhydrous ethanol were added to a three-necked flask and stirred. At room temperature, 10vt% ammonia water was added to the three-necked flask. After the addition was completed, the temperature of the three-necked flask was raised to a micro-reflux state, and the reaction was kept warm for 3-5 hours. After post-treatment, a composite polysiloxane was obtained.

[0023] The synthetic reaction principle of composite polysiloxane is:

[0024]

[0025] A2. Add the composite polysiloxane and methanol into a three-necked flask protected by nitrogen and stir. Raise the temperature of the three-necked flask to a micro-reflux state. Slowly drop the catalyst solution into the three-necked flask. After the addition is complete, keep the temperature for 4-6 hours and perform post-treatment to obtain the siloxane additive.

[0026] The synthetic reaction principle of siloxane additives is:

[0027]

[0028] Furthermore, in step A1, the molar ratio of diethoxymethylsiloxane to diethoxydimethylsilane is 3:5, the dosage ratio of diethoxymethylsilane, anhydrous ethanol and 10vt% ammonia water is 1g:13mL:5mL, and the post-treatment operation includes: after the reaction is completed, the temperature of the three-necked flask is lowered to room temperature, filtered, the filter cake is washed with purified water until neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 65-75°C, and vacuum dried to constant weight to obtain a composite polysiloxane.

[0029] Furthermore, in step A2, the amount ratio of the composite polysiloxane, methanol and catalyst solution is 2g:5mL:1g, and the catalyst solution is composed of tetramethylammonium hydroxide and methanol in a weight ratio of 1:4. The post-treatment operation includes: after the reaction is completed, the temperature of the three-necked flask is reduced to room temperature, a macroporous strongly acidic styrene-based cation exchange resin is added to the three-necked flask, stirred for 30-40 minutes, filtered, and the filtrate is transferred to a rotary evaporator at a temperature of 50-60°C, and methanol is evaporated to obtain a siloxane additive.

[0030] The present invention has the following beneficial effects:

[0031] 1. The flexible PVB resin powder of the present invention is prepared by using polyvinyl alcohol of model 092-52 as a raw material, dissolving it by heating with purified water, and then performing an esterification addition reaction with glacial acetic acid in a mixed catalyst and low temperature environment to form acetate modification on the polyvinyl alcohol to obtain a modified polyvinyl alcohol solution. The acetate group has a high polarity and can enhance the interfacial adhesion between PVB and other materials. The enhancement of the adhesion can improve the aging resistance of PVB after being composited with other materials. The modified polyvinyl alcohol and n-butyraldehyde undergo a condensation reaction to obtain a polyvinyl butyral (PVB) reaction solution. A silane additive with a siloxane-modified long straight-chain siloxane is added to the solution. In an acidic solution, the siloxane bonds on the silane additive are disconnected to react with the active functional groups on the polyvinyl butyral to form a cross-linked structure of silicon oxygen bonding, thereby increasing the cross-linking degree of the PVB resin powder and reducing the hydroxyl content in the PVB resin powder. The PVB resin has a strong The polyvinyl alcohol with good mechanical adhesion, flexibility, smoothness, oil resistance, solvent resistance, protective colloid, gas barrier and wear resistance is used as raw material, and after grafting modification, it is compounded with a silane additive with a long straight-chain siloxane structure to further improve the flexibility of the PVB resin powder; the silane additive itself has a low melting point and viscosity, which improves the fluidity of the resin, reduces the coating viscosity and melt index of the PVB resin, and makes the PVB resin easier to process. The silicon-oxygen bonds in the silane additive molecules have high stability and can maintain stability at high temperatures, so the high temperature resistance of the PVB resin can be improved. At the same time, siloxane can also enhance the interfacial adhesion between the resin and other materials, thereby improving its impact resistance and fatigue resistance, and then improving its damping performance; siloxane has a low refractive index and good light transmittance, which can improve the transparency of the PVB resin and weaken or eliminate the Tyndall effect of the PVB resin.

[0032] 2. The flexible PVB resin powder of the present invention is prepared by using diethoxymethylsilane and diethoxydimethylsilane as reaction monomers, after being uniformly dispersed in anhydrous ethanol, in a reaction system with ammonia water as a catalyst, diethoxymethylsilane and diethoxydimethylsilane undergo hydrolysis and self-assembly reaction to obtain a composite polysiloxane with a long straight chain structure; the composite polysiloxane and methanol undergo a silanol condensation reaction under the action of the catalyst; the hydroxyl groups in the methanol react with the silicon hydrogen on the composite polysiloxane to generate new siloxane bonds to obtain a siloxane additive; in an acidic environment, the siloxane bonds on the siloxane additive are disconnected and react with the hydroxyl groups on the condensate in the PVB resin reaction solution to form a cross-linked structure of silicon oxygen bonding with the PVB resin, thereby reducing the content of hydroxyl groups in the PVB resin, increasing the cross-linking degree of the PVB resin, making the molecular chains compact, increasing the viscosity and damping loss coefficient of the PVB resin, and reducing the Tyndall effect of the PVB resin. DETAILED DESCRIPTION

[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] This embodiment provides a method for preparing ultra-transparent flexible PVB resin powder without Tyndall effect, comprising the following steps:

[0036] S1. Preparation of modified polyvinyl alcohol solution

[0037] Weigh: 20 g of polyvinyl alcohol (model 092-53) and 480 mL of purified water, add them into a three-necked flask and stir, raise the temperature of the three-necked flask to 50° C., stir until the system is dissolved, lower the temperature of the three-necked flask to 20° C., filter and obtain a polyvinyl alcohol solution;

[0038] Add 1.2 g of p-toluenesulfonic acid and 3.6 g of zinc chloride into a three-necked flask and stir for 10 min. Slowly add 0.96 g of glacial acetic acid into the three-necked flask at a dropping rate of 0.2 g / min. After the addition is complete, keep the temperature for reaction for 10 h to obtain a modified polyvinyl alcohol solution.

[0039] S2. Preparation of silane additives

[0040] Weigh: 134.3 g of diethoxymethylsilane, 148.3 g of diethoxydimethylsilane, and 1746 mL of anhydrous ethanol, add them into a three-necked flask and stir, add 671.5 g of 10vt% ammonia water into the three-necked flask at room temperature, and after the addition is complete, raise the temperature of the three-necked flask to a micro-reflux state of the system, keep the temperature for reaction for 3 hours, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain, transfer the filter cake to a drying oven at a temperature of 65°C, and vacuum dry it to constant weight to obtain a composite polysiloxane;

[0041] Add tetramethylammonium hydroxide and methanol in a weight ratio of 1:4 into a beaker and stir evenly to obtain a catalyst solution for later use;

[0042] Weigh: 200 g of composite polysiloxane and 500 mL of methanol are added to a three-necked flask protected by nitrogen and stirred. The temperature of the three-necked flask is increased to a micro-reflux state of the system. 100 g of the catalyst solution is slowly dripped into the three-necked flask. After the addition is completed, the reaction is kept warm for 4 hours. The temperature of the three-necked flask is lowered to room temperature. Macroporous strongly acidic styrene-based cation exchange resin (NKC-9) is added to the three-necked flask to neutralize the pH of the reaction system to 7. The mixture is stirred for 30 minutes and filtered. The filtrate is transferred to a rotary evaporator at 50°C to evaporate the methanol to obtain a solution of the siloxane additive.

[0043] S3. Preparation of PVB resin reaction solution

[0044] Weigh: 500 g of modified polyvinyl alcohol solution, 0.5 g of sodium dodecylbenzene sulfonate and 5 g of 12 mol / L hydrochloric acid, add into a three-necked flask and stir, lower the temperature of the three-necked flask to 10°C, slowly drop 4 g of n-butyraldehyde into the three-necked flask, after the dropwise addition is complete, raise the temperature of the three-necked flask to 56°C, keep warm for 1 hour, and obtain a PVB resin reaction solution.

[0045] S4. Preparation of PVB resin powder

[0046] Add 5 g of silane additive to the three-necked flask containing the PVB resin reaction solution, keep the temperature of the three-necked flask at 56°C, stir for 3 hours, lower the temperature of the three-necked flask to room temperature, add 20 wt% sodium hydroxide solution to the three-necked flask, adjust the system pH to 3, stir for 1 hour, filter, mix the filter cake with purified water in a dosage ratio of 1g:10mL and stir for 20 minutes, filter, wash the filter cake with purified water repeatedly 10 times and transfer it to a drying oven at a temperature of 55°C, vacuum dry to constant weight, crush, and pass through a 60-mesh sieve to obtain PVB resin powder.

[0047] Example 2

[0048] This embodiment provides a method for preparing ultra-transparent flexible PVB resin powder without Tyndall effect, comprising the following steps:

[0049] S1. Preparation of modified polyvinyl alcohol solution

[0050] Weigh: 20 g of polyvinyl alcohol (model 092-53) and 480 mL of purified water, add them into a three-necked flask and stir, raise the temperature of the three-necked flask to 55° C., stir until the system is dissolved, lower the temperature of the three-necked flask to 25° C., filter and obtain a polyvinyl alcohol solution;

[0051] Add 1.2 g of p-toluenesulfonic acid and 3.6 g of zinc chloride into a three-necked flask and stir for 10 min. Slowly add 0.96 g of glacial acetic acid into the three-necked flask at a dropping rate of 0.3 g / min. After the addition is complete, keep the temperature for reaction for 11 h to obtain a modified polyvinyl alcohol solution.

[0052] S2. Preparation of silane additives

[0053] Weigh: 134.3 g of diethoxymethylsilane, 148.3 g of diethoxydimethylsilane, and 1746 mL of anhydrous ethanol, add them into a three-necked flask and stir, add 671.5 g of 10vt% ammonia water into the three-necked flask at room temperature, and after the addition is complete, raise the temperature of the three-necked flask to a micro-reflux state, keep the temperature for 4 hours, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain, transfer the filter cake to a drying oven at a temperature of 70°C, and vacuum dry it to constant weight to obtain a composite polysiloxane;

[0054] Add tetramethylammonium hydroxide and methanol in a weight ratio of 1:4 into a beaker and stir evenly to obtain a catalyst solution for later use;

[0055] Weigh: 200 g of composite polysiloxane and 500 mL of methanol are added to a three-necked flask protected by nitrogen and stirred. The temperature of the three-necked flask is increased to a micro-reflux state of the system. 100 g of the catalyst solution is slowly dripped into the three-necked flask. After the addition is completed, the reaction is kept warm for 5 hours. The temperature of the three-necked flask is lowered to room temperature. Macroporous strongly acidic styrene-based cation exchange resin (NKC-9) is added to the three-necked flask to neutralize the pH of the reaction system to 7.5. The mixture is stirred for 35 minutes and filtered. The filtrate is transferred to a rotary evaporator at 55°C to evaporate the methanol to obtain a solution of siloxane additive.

[0056] S3. Preparation of PVB resin reaction solution

[0057] Weigh: 500 g of modified polyvinyl alcohol solution, 0.5 g of sodium dodecylbenzene sulfonate and 5 g of 12 mol / L hydrochloric acid, add into a three-necked flask and stir, lower the temperature of the three-necked flask to 11°C, slowly drop 4 g of n-butyraldehyde into the three-necked flask, after the dropwise addition is complete, raise the temperature of the three-necked flask to 61°C, keep warm and react for 2 h to obtain a PVB resin reaction solution.

[0058] S4. Preparation of PVB resin powder

[0059] Add 5 g of silane additive to the three-necked flask containing the PVB resin reaction solution, keep the temperature of the three-necked flask at 61°C, stir for 4 hours, lower the temperature of the three-necked flask to room temperature, add 20 wt% sodium hydroxide solution to the three-necked flask, adjust the system pH to 3.5, stir for 1 hour, filter with suction, mix the filter cake with purified water in a dosage ratio of 1g:10mL and stir for 25 minutes, filter with suction, wash the filter cake with purified water repeatedly 10 times and transfer it to a drying oven at a temperature of 60°C, vacuum dry to constant weight, crush, and pass through a 60-mesh sieve to obtain PVB resin powder.

[0060] Example 3

[0061] This embodiment provides a method for preparing ultra-transparent flexible PVB resin powder without Tyndall effect, comprising the following steps:

[0062] S1. Preparation of modified polyvinyl alcohol solution

[0063] Weigh: 20 g of polyvinyl alcohol (model 092-53) and 480 mL of purified water, add them into a three-necked flask and stir, raise the temperature of the three-necked flask to 60° C., stir until the system is dissolved, lower the temperature of the three-necked flask to 30° C., filter and obtain a polyvinyl alcohol solution;

[0064] Add 1.2 g of p-toluenesulfonic acid and 3.6 g of zinc chloride into a three-necked flask and stir for 10 min. Slowly add 0.96 g of glacial acetic acid into the three-necked flask at a dropping rate of 0.4 g / min. After the addition is complete, keep the temperature for reaction for 12 h to obtain a modified polyvinyl alcohol solution.

[0065] S2. Preparation of silane additives

[0066] Weigh: 134.3 g of diethoxymethylsilane, 148.3 g of diethoxydimethylsilane, and 1746 mL of anhydrous ethanol, add them into a three-necked flask and stir, add 671.5 g of 10vt% ammonia water into the three-necked flask at room temperature, and after the addition is complete, raise the temperature of the three-necked flask to a micro-reflux state, keep the temperature for 5 hours, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain, transfer the filter cake to a drying oven at a temperature of 75°C, and vacuum dry it to constant weight to obtain a composite polysiloxane;

[0067] Add tetramethylammonium hydroxide and methanol in a weight ratio of 1:4 into a beaker and stir evenly to obtain a catalyst solution for later use;

[0068] Weigh: 200 g of composite polysiloxane and 500 mL of methanol are added to a three-necked flask protected by nitrogen and stirred. The temperature of the three-necked flask is increased to a micro-reflux of the system. 100 g of the catalyst solution is slowly dripped into the three-necked flask. After the addition is completed, the reaction is kept warm for 6 hours. The temperature of the three-necked flask is lowered to room temperature. Macroporous strongly acidic styrene-based cation exchange resin (NKC-9) is added to the three-necked flask to neutralize the pH of the reaction system to 8. Stir for 40 minutes, filter, and transfer the filtrate to a rotary evaporator at a temperature of 60°C to evaporate methanol to obtain a solution of siloxane additive.

[0069] S3. Preparation of PVB resin reaction solution

[0070] Weigh: 500 g of modified polyvinyl alcohol solution, 0.5 g of sodium dodecylbenzene sulfonate and 5 g of 12 mol / L hydrochloric acid, add into a three-necked flask and stir, lower the temperature of the three-necked flask to 12°C, slowly add 4 g of n-butyraldehyde into the three-necked flask, after the addition is complete, raise the temperature of the three-necked flask to 65°C, keep warm and react for 3 hours to obtain a PVB resin reaction solution.

[0071] S4. Preparation of PVB resin powder

[0072] Add 5 g of silane additive to the three-necked flask containing the PVB resin reaction solution, keep the temperature of the three-necked flask at 65°C, stir for 5 hours, lower the temperature of the three-necked flask to room temperature, add 20 wt% sodium hydroxide solution to the three-necked flask, adjust the system pH to 4, stir for 1 hour, filter, mix the filter cake with purified water at a ratio of 1g:10mL and stir for 30 minutes, filter, wash the filter cake with purified water repeatedly 10 times and transfer it to a drying oven at a temperature of 65°C, vacuum dry to constant weight, crush, and pass through a 60-mesh sieve to obtain PVB resin powder.

[0073] Comparative Example 1

[0074] The difference between this comparative example and Example 3 is that the modified polyvinyl alcohol solution in step S3 is replaced by the polyvinyl alcohol solution in step S1.

[0075] Comparative Example 2

[0076] The difference between this comparative example and Example 3 is that step S2 is eliminated and no silane additive is added in step S4.

[0077] Comparative Example 3

[0078] The difference between this comparative example and Example 3 is that the sodium dodecyl sulfonate in step S3 is replaced by an equal amount of sodium dodecyl succinate.

[0079] Performance Test:

[0080] The butyraldehyde content, polyvinyl acetate content, hydroxyl content, melt index, yellow index, coating-1 cup viscosity, damping loss coefficient and Tyndall effect phenomenon in Example 1-3 and the PVB resin powder prepared in Example 1-3 were tested.

[0081] Test method:

[0082] The butyraldehyde content and polyvinyl acetate content are tested according to the provisions of standard ASTM D1396-1992;

[0083] The hydroxyl content, melt index and yellowness index are tested according to the provisions of standard HG / T6047-2022;

[0084] Tu-1 cup viscosity: weigh 15g of PVB resin powder sample, and then weigh 135g of anhydrous ethanol, mix them evenly, and pour them into the Tu-1 cup for measurement. The cups need to be wiped clean with gauze solvent, and dried, and checked against the light to ensure that the key parts such as the Tu-1 viscometer nozzle are kept clean. Stir the sample to be tested for viscosity evenly, adjust the sample temperature to 20±1℃, place the Tu-1 viscometer in a water bath jacket, insert the stopper rod, introduce the sample into the viscometer, and adjust the horizontal screw to ensure that the liquid level coincides with the scale line. Cover the lid and insert the thermometer, let it stand for a while to allow the bubbles in the sample to overflow. Place a 50mL measuring cup under the viscometer nozzle. When the sample temperature reaches the standard described in the second step, quickly lift the stopper rod and start the stopwatch at the same time. When the sample volume in the cup reaches the 50mL scale line, stop the stopwatch immediately. The event required for the sample to flow into the cup for 50mL is the sample outflow time, and the average of the two measurements is taken as the measurement result. The difference between the two measured values ​​is not more than 3% of the average value;

[0085] Damping loss coefficient: PVB resin powder is extruded into a sound insulation PVB interlayer with a thickness of 0.1 mm, and then tested according to the provisions of ISO16940-2008;

[0086] High temperature resistance: Weigh 5g of PVB resin powder, place it on a 15cm×15cm glass slide, flatten the PVB resin powder into a circle with a diameter of 10cm, bake it in an oven at 180℃ for 30 minutes, and measure the sulfonic acid index of the sample;

[0087] Tyndall effect phenomenon: Mix 15g PVB resin powder and 5g plasticizer and stir evenly, then put them into a vacuum drying oven for baking at 180℃ for 1h, then take them out for cooling and observe them under a D65 standard light source to see if there is any Tyndall effect.

[0088] The specific test results are shown in the table below:

[0089]

[0090]

[0091] Data Analysis:

[0092] By comparing and analyzing the data in the above table, the hydroxyl content of the PVB resin powder prepared by the present invention is reduced to 10.5%, the melt index is increased to 1.34g / 10min, the coating-1 cup viscosity reaches 222s, the damping loss coefficient is increased to 0.26, the yellow index before baking reaches 2.14, and the yellow index after baking reaches 2.16, and no Tyndall effect is produced, indicating that the PVB resin powder prepared by the present invention not only has rich cross-linking bonds, but also reduces the hydroxyl content therein, has a high melt index, and is easier to process and form, and the damping loss coefficient of the film prepared by the PVB resin powder is high, which is helpful for sound insulation and noise reduction. Before and after baking, the yellow index of the PVB resin powder changes little, indicating that the PVB resin powder prepared by the present invention has excellent high temperature aging resistance in a high temperature environment; in the experimental process, triethylene glycol diisooctanoate is selected as a plasticizer, and when the weight ratio of PVB resin powder to triethylene glycol diisooctanoate is 3:2 to 1:2, the good optical properties and compatibility of the super-transparent type without Tyndall effect can still be maintained.

[0093] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0094] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0095] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing ultra-transparent flexible PVB resin powder without Tyndall effect, characterized in that: The following steps are involved: S1. Add polyvinyl alcohol and purified water into a three-necked flask and stir. Raise the temperature of the three-necked flask to 50-60°C and stir until the system is dissolved. Lower the temperature of the three-necked flask to 20-30°C and filter to obtain a polyvinyl alcohol solution. S2, adding the polyvinyl alcohol solution and the catalyst to a three-necked flask and stirring, lowering the temperature of the three-necked flask to 20-30 ° C, slowly dropping glacial acetic acid into the three-necked flask, and keeping the temperature for reaction for 10-12 hours to obtain a modified polyvinyl alcohol solution, wherein the weight ratio of the polyvinyl alcohol solution, the catalyst and the glacial acetic acid is 500:3:1, the catalyst is composed of p-toluenesulfonic acid and zinc chloride in a weight ratio of 1:3, and the dropping rate of the glacial acetic acid is 0.2-0.4g / min; S3, adding the modified polyvinyl alcohol solution, the surfactant and the inorganic acid into a three-necked flask and stirring, the temperature of the three-necked flask is reduced to 10-12 ° C, and n-butyraldehyde is slowly added dropwise to the three-necked flask. After the addition is completed, the temperature of the three-necked flask is increased to 56-65 ° C, and the reaction is kept warm for 1-3 hours to obtain a PVB resin reaction solution, wherein the weight ratio of the modified polyvinyl alcohol solution, the surfactant, the inorganic acid and n-butyraldehyde is 500:0.5:5:4, the surfactant is sodium dodecylbenzene sulfonate, and the inorganic acid is 12 mol / L hydrochloric acid; S4, adding a silane additive to a three-necked flask containing a PVB resin reaction solution, keeping the temperature of the three-necked flask at 56-65°C, stirring for 3-5h, and post-processing to obtain PVB resin powder, wherein the weight ratio of the silane additive to the modified polyvinyl alcohol solution in step S3 is 5:700, and the post-processing operation includes: after the reaction is completed, lowering the temperature of the three-necked flask to room temperature, adding a 20wt% sodium hydroxide solution to the three-necked flask, adjusting the system pH to 3-4, stirring for 1h, filtering by suction, mixing the filter cake with purified water at a dosage ratio of 1g:10mL and stirring for 20-30min, filtering by suction, repeatedly washing the filter cake with purified water 10 times, and then transferring it to a drying oven at a temperature of 55-65°C, vacuum drying to constant weight, crushing, and passing through a 60-mesh sieve to obtain PVB resin powder; Silane additives are processed by the following steps: A1. Diethoxymethylsilane, diethoxydimethylsilane and anhydrous ethanol were added to a three-necked flask and stirred. At room temperature, 10 vol% ammonia water was added to the three-necked flask. After the addition was completed, the temperature of the three-necked flask was raised to a micro-reflux state, and the reaction was kept warm for 3-5 hours. After post-treatment, a composite polysiloxane was obtained. A2. Add the composite polysiloxane and methanol into a three-necked flask protected by nitrogen and stir. Raise the temperature of the three-necked flask to a micro-reflux state. Slowly drop the catalyst solution into the three-necked flask. After the addition is complete, keep the temperature for 4-6 hours and perform post-treatment to obtain the siloxane additive.

2. The method for preparing a super-transparent flexible PVB resin powder without Tyndall effect according to claim 1, characterized in that: The weight ratio of polyvinyl alcohol to purified water in step S1 is 1:

24.

3. The method for preparing a super-transparent flexible PVB resin powder without Tyndall effect according to claim 1, characterized in that: In step A1, the molar ratio of diethoxymethylsiloxane to diethoxydimethylsilane is 3:5, the dosage ratio of diethoxymethylsilane, anhydrous ethanol and 10 vol% ammonia water is 1 g: 13 mL: 5 mL, and the post-treatment operation includes: after the reaction is completed, the temperature of the three-necked flask is lowered to room temperature, filtered, the filter cake is washed with purified water until neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 65-75 ° C, and vacuum dried to constant weight to obtain a composite polysiloxane.

4. The method for preparing a super-transparent flexible PVB resin powder without Tyndall effect according to claim 1, characterized in that: In step A2, the amount ratio of the composite polysiloxane, methanol and the catalyst solution is 2g:5mL:1g, and the catalyst solution is composed of tetramethylammonium hydroxide and methanol in a weight ratio of 1:

4. The post-treatment operation includes: after the reaction is completed, the temperature of the three-necked flask is reduced to room temperature, a macroporous strongly acidic styrene-based cation exchange resin is added to the three-necked flask, stirred for 30-40 minutes, filtered, and the filtrate is transferred to a rotary evaporator at a temperature of 50-60°C, and methanol is evaporated to obtain a siloxane additive.

Citation Information

Patent Citations

  • Polyvinyl butyral with sound insulation performance, and preparation method thereof

    CN113861315A

  • Synthesis process of low-volatile and odorless polyvinyl butyral resin powder

    CN116082540A